End-of-life decision-making capacity in an elderly patient with schizophrenia and terminal cancer - Carla Kotze; Johannes L. Roos (South African Family Practice)
Medical practitioners are confronted daily with decisions about patients’ capacity to consent to interventions. To address some of the pertinent issues with these assessments, the end-of-life decision-making capacity of a 72-year-old female with treatment-resistant schizophrenia and terminal cancer is discussed, as are the role of the treating clinician and the importance of health-related values. There is a recommendation that the focus of these assessments can rather be on practical outcomes, especially when capacity issues arise. This implies that the decision-making capacity of the patient is only practically important when the treatment team is willing to proceed against the patient’s wishes. This shifts the focus from a potentially difficult assessment to the simpler question of whether the patient’s capacity will change the treatment approach. Clinicians should attend to any possible underlying issues, instead of focusing strictly on capacity. Compared to the general populations people with serious mental illness (SMI) have higher rates of physical illness and die at a younger age, but they do not commonly access palliative care services. Conversations about end-of-life care can occur without fear that a person’s psychiatric symptoms or related vulnerabilities will undermine the process. More research about palliative care and advance care planning for people with SMI is needed. This is even more urgent in light of the coronavirus disease-2019 (COVID-19) pandemic, and South African health services should consider recommendations that advanced care planning should be routinely implemented. These recommendations should not only focus on the general population and should include patients with SMI.